2015
DOI: 10.1186/s12284-015-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Rice arbuscular mycorrhiza as a tool to study the molecular mechanisms of fungal symbiosis and a potential target to increase productivity

Abstract: Rice (Oryza sativa L.) is a monocot model crop for cereal molecular biology. Following the emergence of molecular genetics of arbuscular mycorrhizal (AM) symbiosis in model legumes in the 1990s, studies on rice genetic resources have considerably contributed to our understanding of the molecular mechanisms and evolution of root intracellular symbioses.In this review, we trace the history of these studies and suggest the potential utility of AM symbiosis for improvement in rice productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
0
8
0
2
Order By: Relevance
“…Glomus was the most frequently encountered AMF phylotype in all regions, except for the Ashanti region. The predominance of Glomus phylotypes in rice plants was revealed by several studies, irrespective of the conventional (wet paddy) system or production under rain-fed conditions [49][50][51]62]. The consistent occurrence of Glomus in these varying conditions of production indicated that the genus Glomus could withstand several environmental conditions and was adapted to various ecosystems [40,61].…”
Section: Discussionmentioning
confidence: 99%
“…Glomus was the most frequently encountered AMF phylotype in all regions, except for the Ashanti region. The predominance of Glomus phylotypes in rice plants was revealed by several studies, irrespective of the conventional (wet paddy) system or production under rain-fed conditions [49][50][51]62]. The consistent occurrence of Glomus in these varying conditions of production indicated that the genus Glomus could withstand several environmental conditions and was adapted to various ecosystems [40,61].…”
Section: Discussionmentioning
confidence: 99%
“…2 ; 37, 47, 54, 59). Non-leguminous plants have mutualistic symbiotic relationships with arbuscular mycorrhizal fungi through the CSP ( 37 , 42 , 55 ). Ca 2+ /calmodulin–dependent protein kinase (encoded by CCaMK ) has been identified as a key component of the CSP, which is required for rhizobial and mycorrhizal endosymbioses to take up N and phosphorus, respectively ( 37 , 47 , 54 56 , 59 ).…”
Section: Plant Genes For Microbial Symbiosesmentioning
confidence: 99%
“…We also developed a Falcon-wick hydroponics system for larger AM model plants. We choose the important crop and model plant rice, because it currently represents the prime monocots model for studying molecular mechanisms of mycorrhizal colonization (Nakagawa and Imaizumi-Anraku, 2015). We grew rice in a bigger hydroponics system using Falcon tubes instead of pipette tips as a support (Falcon-wick system, Figure 5).…”
Section: Falcon-wick Hydroponics For Colonization Of Rice Roots By Armentioning
confidence: 99%